A novel coating method for MoO3 to improve the electrochemical performance of regenerated Li(Ni0.8Co0.1Mn0.1)O2 cathode material from spent Li‐ion Batteries. Issue 18 (10th May 2022) - Jin, Shan; Xu, Yuanxiang; Liang, Jianquan; Zhang, Jian; Wang, Yue; Mu, Deying; Dai, Changsong
Abstract: Regeneration of cathode materials from spent lithium‐ion batteries (LIBs), as an efficient short‐range recycling strategy, is gradually becoming a research hotspot. However, due to the unavoidable influence of impurities in the recycling process, the regenerated material suffers from severe performance degradation during the recycling process. Surface coating is an effective routine to improve cycling stability. Here, regenerated Li(Ni0.8 Co0.1 Mn0.1 )O2 cathode material is successfully wet‐coated by an appropriate amount of MoO3 . The study finds the material loading 2.0 wt% MoO3 exhibits even better properties. After 100 cycles, the capacity retention efficiency is significantly improved from 70 % to 86.5 % in the range of 2.8∼4.3 V. It is confirmed that the MoO3 coating effectively stabilized the cathode/electrolyte interface, thus reducing the occurrence of side reactions and improving the electrochemical stability of the battery. In addition, the MoO3 had great electrical conductivity, keeping the lithium diffusion even at a stable level upon cycling. To sum up, our work provides a simple and available modification strategy for nickel‐rich cathode materials recovered from spent LIBs. Abstract : A novel coating method for MoO3 has been investigated in regenerated Li(Ni0.8 Co0.1 Mn0.1 )O2 cathode material from spent LIBs to achieve a significant improvement in electrochemical performance. This work demonstrates the application prospect of MoO3 coating in sustainable recycling and reusing of spent lithium‐ion batteries and also suggests a feasible, general modification strategy for similar regenerated cathode materials.